LEADERSHIP AND MOTIVATION: STRATEGIES TO LEAD AND MOTIVATE SALES TEAMS TO ACHIEVE GOALS AND IMPROVE PERFORMANCE - Elva, Andreia Alves da Silva (LUMEN ET VIRTUS, 2023)
In today’s highly competitive and rapidly evolving business environment, the effectiveness of sales teams is closely tied to the quality of leadership and the application of motivational strategies. This article examines how leadership styles—particularly transformational leadership—combined with evidence-based motivational theories, such as Self-Determination Theory and Goal-Setting Theory, can significantly enhance sales performance. It discusses the role of autonomy, recognition, team cohesion, and psychological safety in fostering sustained motivation and engagement among sales professionals. Furthermore, the article explores the impact of non-financial incentives, continuous professional development, and inclusive workplace cultures on employee commitment and output. By integrating leadership practices with motivational principles, organizations can empower their sales teams to achieve ambitious goals, adapt to market changes, and maintain a high level of performance. The findings underscore the importance of strategic and empathetic leadership in cultivating resilient, motivated, and results-driven sales teams.